2008
DOI: 10.1111/j.1365-2761.2007.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on pharmacokinetics of enrofloxacin in mud crab, Scylla serrata (Forsskål), following oral administration

Abstract: The study was conducted to evaluate the pharmacokinetics of enrofloxacin following a single oral gavage (10 mg kg(-1)) in mud crab, Scylla serrata, at water temperatures of 19 and 26 degrees C. Enrofloxacin concentration in haemolymph was determined using high-performance liquid chromatography (HPLC). A multiple and repeated haemolymph sampling from the articular cavity of crab periopods was developed. The haemolymph of an individual crab was successfully sampled up to 11 times from the articular cavity. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
15
1
Order By: Relevance
“…Our studies with sea stars showed an elimination T½ after injection was approximately 43 hr, which was similar to the T½ in the giant freshwater prawn following oral administration, but longer than the T½ of the European cuttlefish, Manila clam, ridgetail white prawn ( Exopalaemon carinicauda ), and green sea urchin ( Strongylocentrotus droebachiensis ) (Chang, Gao, Li, & Liu, ; Gore et al., ; Liang et al., ; Phillips et al., ; Poapolathep et al., ). In Chinese mitten‐handed crabs ( Eriocheir sinensis ) that received 5 mg/kg enrofloxacin injection, and mud crabs that received 10 mg/kg enrofloxacin orally (Fang et al., ; Wu, Meng, Zhu, & Huang, ), the T½ of enrofloxacin was 52.4 hr and 79 or 56 hr (depending on temperature), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies with sea stars showed an elimination T½ after injection was approximately 43 hr, which was similar to the T½ in the giant freshwater prawn following oral administration, but longer than the T½ of the European cuttlefish, Manila clam, ridgetail white prawn ( Exopalaemon carinicauda ), and green sea urchin ( Strongylocentrotus droebachiensis ) (Chang, Gao, Li, & Liu, ; Gore et al., ; Liang et al., ; Phillips et al., ; Poapolathep et al., ). In Chinese mitten‐handed crabs ( Eriocheir sinensis ) that received 5 mg/kg enrofloxacin injection, and mud crabs that received 10 mg/kg enrofloxacin orally (Fang et al., ; Wu, Meng, Zhu, & Huang, ), the T½ of enrofloxacin was 52.4 hr and 79 or 56 hr (depending on temperature), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al. () showed that higher water temperatures (26° vs 19°C) was a significant factor by increasing clearance of enrofloxacin. Future studies to consider the effect of temperature has on the pharmacokinetics of enrofloxacin in horseshoe crabs would be of value.…”
Section: Discussionmentioning
confidence: 99%
“…However, with oxytetracyline treatment t ½ α and t ½ β values were larger in finfish than crustaceans. Fang et al(2008) considered an open circulatory system in crustaceans, as contrasted to closed systems in finfish, as another reason for differences in certain pharmacokinetic parameters between crustaceans and finfish.…”
Section: Factors That Have An Influence On Pharmacokineticsmentioning
confidence: 99%
“…Crustaceans, including crabs and shrimp, are the preferred invertebrates used as research objects. Plasma concentration-time data has been best fitted in open two-compartmental models following intramuscular injection in species such as P. monodon, L. s. setiferus (Reed et al, 2004) and S. serrata (Fang et al, 2008). Whereas the pharmacokinetics of oxytetracyline in A. anguilla and O. mykiss after oral administration were described by a one compartmental model, oxytetracyline blood concentration-time curves of O. tshawytscha and O. mykiss treated through the intra-arterial route were simulated by a three-compartmental open pharmacokinetic model.…”
Section: Pharmacokinetics Models and Parametersmentioning
confidence: 99%
See 1 more Smart Citation